Studi Deskriptif Mengenai Manajemen Risiko Pada Usaha Penyewaan Alat Camping Lentera Camp di Bandung - Ahmad Ryansyah Ramadhan; Muhammad Irfan Fauzan; Zaid Abdul Hamid; Dea Wisnu Ramdani; Berdhy Ursila Djamil (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines the application of risk management using ISO 31000:2018 to minimize potential losses and improve operational effectiveness within an organization. Through the processes of risk identification, analysis, evaluation, and control, companies can understand potential risk sources and determine appropriate mitigation actions. This study highlights the importance of risk mapping based on probability and impact levels, allowing organizations to establish more accurate handling priorities. The findings show that implementing a structured risk management framework can reduce operational disruptions, enhance decision-making quality, and support business sustainability.